2020
DOI: 10.1002/adfm.202005769
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Vascular Grafts That Grow with the Host

Abstract: Cell-free small diameter vascular grafts, based on small intestinal submucosa functionalized with heparin and vascular endothelial growth factor (VEGF) are manufactured and implanted successfully into the arterial system of neonatal lambs, where they remain patent and grow in size with the host to a similar extent and with similar rate as native arteries. Acellular tissue engineered vessels (A-TEVs) integrate seamlessly into the native vasculature and develop confluent, functional endothelium that affords pate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Cardiovascular disease is the leading cause of death worldwide, being associated with high morbidity and mortality. The increase of both arterial occlusive diseases and coronary heart diseases leads to a higher demand for small-diameter vascular grafts (<6 mm). The gold standard for small-diameter vessel replacement is the use of autologous veins, such as the saphenous and umbilical veins, the internal thoracic, and the radial artery. ,, However, due to the limited availability of healthy autologous vessels (associated with patient age and consequently blood vessel quality), there is a clinical demand for functional and long-term testing small-caliber blood vessel grafts. ,,, Although synthetic polymers have been successfully used for the replacement of large-diameter vascular grafts (>6 mm), they are associated with thrombosis, intimal hyperplasia, calcification, and chronic inflammation when used as small-diameter vascular grafts. , Moreover, synthetic polymers do not have the capacity to grow overtime. , Natural materials have been investigated for this application.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death worldwide, being associated with high morbidity and mortality. The increase of both arterial occlusive diseases and coronary heart diseases leads to a higher demand for small-diameter vascular grafts (<6 mm). The gold standard for small-diameter vessel replacement is the use of autologous veins, such as the saphenous and umbilical veins, the internal thoracic, and the radial artery. ,, However, due to the limited availability of healthy autologous vessels (associated with patient age and consequently blood vessel quality), there is a clinical demand for functional and long-term testing small-caliber blood vessel grafts. ,,, Although synthetic polymers have been successfully used for the replacement of large-diameter vascular grafts (>6 mm), they are associated with thrombosis, intimal hyperplasia, calcification, and chronic inflammation when used as small-diameter vascular grafts. , Moreover, synthetic polymers do not have the capacity to grow overtime. , Natural materials have been investigated for this application.…”
Section: Introductionmentioning
confidence: 99%
“…In an intriguing recent study, heparin and VEGF modified SIS tubes showed the growth potential in an ovine carotid artery implantation model. The integrated grafts integrated seamlessly with the host artery and grew in size with the host age over 6 months, evincing their remarkable ability to solve the current clinical limitations for pediatric patients; [ 176 ] however further validation is required for their clinical implementation.…”
Section: Emerging Strategies To Improve the Tevg Performancementioning
confidence: 99%
“…The grafts were treated with heparin and pre-seeded with SMCs and implanted into sheep for 90 days. After the culture period, the grafts exhibited lumens with no sign of intimal hyperplasia or clotting [209]. The grafts with pre-seeded SMCs had a higher concentration of collagen content, indicating cellular maturation [209].…”
Section: Translational Applications Of Ecm-based Biomaterials 61 Engineered Vascular Graftsmentioning
confidence: 99%
“…After the culture period, the grafts exhibited lumens with no sign of intimal hyperplasia or clotting [209]. The grafts with pre-seeded SMCs had a higher concentration of collagen content, indicating cellular maturation [209]. Table 6 summarizes the 2D tissues for vascular grafts.…”
Section: Translational Applications Of Ecm-based Biomaterials 61 Engineered Vascular Graftsmentioning
confidence: 99%